Prevalence and Severity of Gastrointestinal Symptoms in Recreational and Elite Equestrian Athletes in Training and Competition: An Exploratory Analysis - Russ Best; Jeni Pearce (International Journal of Equine Science)
Equestrian sports present a unique challenge to the rider's gastrointestinal (GI) tract and health as they meet nutritional requirements for performance, execute riding discipline-specific skills, and coordinate their hip and abdominal movements with their equine movement pattern. Additional gastrointestinal challenges may result from the known gut-brain axis, as previous research reports a high rate of anxiety in equestrian athletes. A survey was administered to assess the prevalence and severity of gastrointestinal symptoms in recreational and elite equestrian athletes across a range of disciplines. Participants reported the prevalence of 12 symptoms on a 0–10 point scale and stool consistency using a modified validated questionnaire. Total symptom score, symptom perception, and symptom region (Upper GI tract, Lower GI tract, and Other) were assessed. A subset of elite riders repeated the questionnaire post-competition. Elite riders had a higher average total GI symptom score but did not differ significantly from the recreational sample (W = 438.50; p = 0.13; rB = 0.19; Small). There were no regional symptom differences between groups. The prevalence of all abnormal stool consistencies was higher in the elite sample compared to the recreational sample. Five elite athletes (25%) reported blood in the stool. Symptoms are not correlated with nor predicted by rider age or number of competitions performed per year (all p > 0.05; R2 = 0.10–0.59). Symptoms were not significantly different in competition. The majority of equestrians present with some GI symptoms, with a small proportion of elite and recreational riders showing symptoms that impair exercise performance. The questionnaire provides a useful starting point for athletes, coaches, and support personnel to understand the prevalence and severity of symptoms in equestrians.